2017
DOI: 10.1189/jlb.4a0217-042r
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Toll-like receptor 2–mediated proinflammatory responses by Mycobacterium tuberculosis protein Rv3529c

Abstract: Microorganisms are known to devise various strategies to thwart protective responses by the host. One such strategy is to incorporate sequences and domains in their genes/proteins that have similarity to various domains of the host proteins. In this study, we report that protein Rv3529c exhibits significant similarity to the death domain of the TLR pathway adaptor protein MyD88. Incubation of macrophages with Rv3529c specifically inhibited TLR2-mediated proinflammatory responses. This included attenuated oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Our previous study also reported another tuberculosis protein EspR, which could bind to MyD88 and inhibit the TLR pathway activation as well as subsequent macrophage inflammation [33]. In line with our data, Bandyopadhyay U and colleagues [34] showed that Mtb protein Bone marrow derived macrophages (BMDMs) were prepared as previously described [33].…”
Section: Discussionsupporting
confidence: 80%
“…Our previous study also reported another tuberculosis protein EspR, which could bind to MyD88 and inhibit the TLR pathway activation as well as subsequent macrophage inflammation [33]. In line with our data, Bandyopadhyay U and colleagues [34] showed that Mtb protein Bone marrow derived macrophages (BMDMs) were prepared as previously described [33].…”
Section: Discussionsupporting
confidence: 80%
“…The ability to degrade cholesterol is a well-known virulence determinant for M. tuberculosis [5860]. Sterol catabolism is thought to provide carbon for both growth and respiration [61], as well as providing a mechanism to manipulate the host cell’s immune response [62]. In BCG Danish, transposon insertions in many of the genes involved in cholesterol metabolism were found to be attenuating, in particular genes of the igr operon [63], which degrade the cholesterol side chain [45], and hsaC together with many of the genes of the kstR2 regulon [46].…”
Section: Discussionmentioning
confidence: 99%
“…MprA and MprA* were biotinylated with NHS-Biotin and subsequently conjugated with streptavidin-phycoerythrin (Strep-PE) (Chadha et al, 2015;Mehto et al, 2015;Bandyopadhyay et al, 2017). PMA-treated THP-1 cells were incubated with 15 μ g/ml of biotin-streptavidinphycoerythrin (PE) conjugated MprA and MprA*followed by dialysis to get rid of unbound biotin-streptavidin-phycoerythrin (PE) conjugate.…”
Section: Uptake and Intra-cellular Detection Of Mpra And Mpra*mentioning
confidence: 99%
“…It is well established that increased calcium concentration in infected cells promote this fusion and M.tuberculosis down modulates calcium levels upon infection (Malik et al, 2000;Malik et al, 2003). We recently showed that M.tuberculosis protein Rv3529c inhibits the fusion of phagosomes with lysosomes that is promoted by increased influx of calcium mediated by the calcium ionophore, ionomycin (Bandyopadhyay et al, 2017). We therefore, used the same strategy to investigate the role of MprA and MprA* in modulating phago-lysosome fusion.…”
Section: Mpra Promotes Macrophage Survivalmentioning
confidence: 99%